حزب مفدال الصهيوني الدينى وموقفه من عملية السلام الإسرائيلى الفلسطيني 1990-2000 (JOURNAL OF INDONESIAN ISLAM, 2008)
This article looks at the potentialities of a Jewish religious group called Mifdel as an obstacle to the Israeli-Palestinian peace process in the period 1990-2000. Generally, the international and regional context in the first decade of the peace process indicated a situation conducive to an interim and final settlement of the conflict. However, the two sides merely reached  a partial settlement and failed in the more essential final settlement. The focus on Mifdel does not mean ignoring the role of other groups such as the hawkish wing of the Likud party and Moledet, the Islamic movement Hamas, and Jihad Islamic movements that still have an unrealistic outlook. This paper shows that Mifdel’s ideology, as it is implanted, radicalized and propagated, was an important source of  resistance against the Israeli-Palestinian peace negotiations. For Indonesian Muslims, the Middle Eastern conflicts, especially the Palestinian-Israeli conflict, have caused very complicated problems. Regarded by some as religious conflicts these Middle Eastern tensions have influenced very much the dynamics of Muslim communities in Indonesia.